REKONSTRUKSI REGULASI PEMBIAYAAN PENDIDIKAN ISLAM BERBASIS KEADILAN DAN KEBERLANJUTAN DI ERA DISRUPSI DIGITAL DAN KETIDAKPASTIAN EKONOMI - M. Mashuri Nurkulla; Herwina Bahar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic education financing in Indonesia faces increasingly complex challenges due to digital disruption and global economic uncertainty. Although various regulations have provided legal foundations for educational financing, their implementation remains fragmented and has not fully reflected the principles of social justice and sustainability. This study aims to analyze the existing conditions of Islamic education financing regulations, examine the implementation of justice principles in financing practices, identify challenges emerging from digital disruption and economic uncertainty, and formulate a reconstruction model of financing regulations based on justice and sustainability principles. This study employed a qualitative library research approach by examining legal documents, scientific literature, and policy reports related to Islamic education financing. The findings indicate that Islamic education financing regulations remain sectoral and have not optimally integrated state financing with Islamic philanthropic instruments such as zakat, infaq, sadaqah, and waqf. Furthermore, digital transformation and economic instability require a more adaptive, innovative, and resilient financing system. Therefore, an integrative regulatory reconstruction model emphasizing social justice, financing sustainability, digital adaptation, and good governance is necessary to establish an inclusive and sustainable Islamic education financing system.